Menangani Kesehatan Mental di Sekolah : Peran Manajemen Kelas Yang Efektif - Anisa, Zahro; A'yun, Qurrotul; Agus R, Abu Hasan; Na'iesa, Sitti; Aini, Tsamar Nur (UMSU, 2024)
This study aims to identify the most effective classroom management strategies for improving the psychological wellness of students, with particular emphasis on techniques that involve technological integration and relationships. The main focus of contemporary learning has shifted to the integration of management strategies to improve students' psychological wellness holistically, rendering this study's conclusion of paramount significance. Utilizing a qualitative descriptive methodology, information can be collected through techniques for collecting information from observations, and documentation, including the ones. After gathering information, evaluation uses triangulation information to ensure information accuracy and reliability. The research findings indicate that this matters most to provide an empowering and nurturing learning environment, conduct social-emotional learning programs, provide stress and anxiety relief, and use technology to improve the psychological well-being of pupils. One of this study's advantages is to provide more insight into the best practices. This study aims to provide more understanding of the best practices for classroom management that can improve students' overall well-being or provide the basis for future research into better teaching methods including policies.